History of Karakoram Highway (Vol.2) : The Karakoram Highway - Mumtaz Khalid, Muhammad Brigadeir; Edited by Akmal, Parvez Major General (Rawalpindi, Pakistan Hamza Pervez Printers, 2009)
A history of how the Sappers of the Pakistan Army Corps of Engineers built the Karakoram Highway through the rugged terrain of Pakistan.
Include Illustration, Maps and Index
Keywords: Roads -- Pakistan -- Roads -- Pakistan -- History